PENGARUH PERBANDINGAN JENIS GULA AREN (Arenga pinnata Merr) TERHADAP MUTU SENSORIS HALUA KACANG TANAH (Arachis hypogeae L.) - Linda E. Ulaan; Maya M. Ludong; Dekie Rawung; Tineke M. Langi (COCOS, 2015)
ABSTRACTPalm sugar is a sweetener that has been used in Indonesian for long time. Palm sugar is made from the sap of palm trees (Arenga pinnata Merr) and includes plants of the palm family and contains sucrose and reducing sugars (glucose and fructose). In North Sulawesi, palm sugar is largely produced in South Minahasa regency. There are 2 types of sugar that is processed and marketed by the local term minahasa called balemantah palm sugar (dry sugar) and batali palm sugar (Sugar Wet). One of the products processed from palm sugar is peanuts halua.This study aims to determine the right formulas of type of palm sugar in the manufacture halua traditionally based on the results of sensory tests to taste, color, aroma and texture. The experiment was averanged in completely randomized design (CRD) with three repetitions.The results showed that the best product was obtained from the ratio of 85% palm sugar balemantah: 15% batali palm sugar. Halua peanuts has a water content; 4.9% sugar; 72.48% color 3.7 (like); taste 3.6 (like); aroma 3.6 (like); texture 3.7 (like).Keywords: Balemantah palm sugar, batali palm sugar, peanuts halua